The effects of the imposition of the French protectorate in 1912 on the Far Maghreb - Al-Azzawi, Ammar Rashid Jabouri; Al Salman, Anam Mahdi Ali (Al-Adab Journal, 2021)
This study tries - as much as possible - to paint a clear picture of an important and decisive stage in the history of the Far Maghreb, which is an extension of Arab-Islamic history, by studying the political, social and economic developments that Morocco went through when it was forced to sign a protection contract with France in 1912. As the study was divided into three axes. The first axis shows the nature of the Moroccan people, its social and ethnic components, and the nature of the ruling system prevailing in it for centuries. As for the second axis, it shed light on the nature of the European struggle in order to control the capabilities of Morocco and its colonization and how France was able to monopolize Morocco. As for the third axis, it explained the terms of the protection treaty imposed by France on Morocco with international approval. And how to implement these provisions that stripped the Sultan, his government and his people of all their rights. As for the sources of this study, they were varied, including Arabic, Arabized, and some English and French sources. Which gave the study the necessary information, especially the book of historian Abd al-Hadi al-Tazi (The French Protectorate - Its Beginning and End). And the book Al-Hashemi Filali (Lessons in the History of Morocco) We concluded the study with a conclusion in which we tried to give the results we reached, through which we can learn about the state of Morocco’s maximum conditions after the imposition of the French protection and how it robbed it of its independence.